Index Morphotectonic Of Morphology In The Patukuki Watershed Region, Peling Tengah District, Banggai Kepulauan - Sukardan Tawil; Bayu Saputra; Abdul Mukaddas; Asrafil (Tadulako Science and Technology Journal, 2021)
Introduction: The Patukuki area in the Central Peling sub-district falls administratively within the geographical coordinates of 123°01'00" – 123°01'3" longitude and 01°24'00" – 01°27'00" latitude. Method: Channel Sinuosity (S) measures river influence on landscapes by comparing actual river length to valley length. Mountain-front sinuosity (Smf) evaluates mountain-front curvature using base and straight-line lengths. The Valley Floor Width to Width-to-height ratio (Vf) identifies regions of rapid uplift, with lower values indicating higher activity. The Asymmetric Factor (AF) detects tectonic tilting in drainage basins by comparing the area of the right-hand side sub-basin to the total area. Results and Discussion: Based on the analysis conducted, the findings are as follows: Channel Sinuosity analysis shows that sub-bases 1, 2, and 3 have high tectonic activity, while sub-base 5 has moderate activity, and sub-base 3 is low. Stream Morphology Frequency (Smf) analysis shows moderate tectonic activity in sub-bases 1, 3, 4, and 5, and sub-base 2 with an average Smf value of more than 1.5. Valley floor width to height ratio (Vf) shows low tectonic activity in all sub-bases. Anisotropy of Magnetic Susceptibility (AF) shows that sub-bases 1 and 5 have high tectonic activity, sub-bases 3 and 4 are moderate, and sub-base 3 is low. The IATR values of sub-bases 1, 4, and 5 are between 1.5 and less than 2, while sub-bases 2 and 3 show moderate tectonic activity with IATR values between 2 and less than 2.5.Conclusion: In summary, tectonic activity in the Patukuki watershed ranges from moderate to high based on the various analyzed indices.